Improving the Efficiency of Corporate Governance in Enterprises in the Electric Power Sector - Samiev Shakhrukh (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This scientific article explores the reforms and their results in increasing the efficiency of corporate governance in enterprises in the electric power sector, the problems that persist in the network, the problems in the regulation and management of the electric power sector, and gives suggestions and recommendations on ways to eliminate them.